2012
DOI: 10.1111/j.1439-0523.2012.01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving in vivo maize doubled haploid production efficiency through early detection of false positives

Abstract: With 1 figure and 2 tables Abstract In vivo doubled haploid (DH) technology provides a means of creating new maize inbred lines relatively quickly; however, productivity is limited by false‐positive (FP) plants for haploidy and for dihaploidy, which consume resources of space and labour until detected. This work examines the potential for using stomata guard cell length measurement as a means for early detection of FP plants. We found that the true haploid and DH plants could be differentiated from FP and untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 11 publications
3
49
0
7
Order By: Relevance
“…As demonstrated with ten populations in this study, use of seedling traits along with Navajo marker can reduce the FDR by several-fold compared to use of Navajo marker alone. Other methods proposed for identification of false positives include purple stem color marker (Röber et al 2005), differences in guard cell measurements (Choe et al 2012), flow cytometry (Dang et al 2012;de Couto et al 2013), and red root marker (Chaikam et al 2016). Purple stem marker develops only after sufficient vegetative growth (Chaikam et al 2016) and for conducting guard cell measurements and flow cytometry need sufficient growth to collect tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated with ten populations in this study, use of seedling traits along with Navajo marker can reduce the FDR by several-fold compared to use of Navajo marker alone. Other methods proposed for identification of false positives include purple stem color marker (Röber et al 2005), differences in guard cell measurements (Choe et al 2012), flow cytometry (Dang et al 2012;de Couto et al 2013), and red root marker (Chaikam et al 2016). Purple stem marker develops only after sufficient vegetative growth (Chaikam et al 2016) and for conducting guard cell measurements and flow cytometry need sufficient growth to collect tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Dang et al (2012) observed rates of duplicated plants ranging from 28% to 54%. Battistelli et al (2013), in turn, obtained a higher percentage of duplicated plants, ranging from 59.1% to 80%, whereas the percentages of plants duplicated by Choe et al (2012) varied from 5% to 57.1% in the evaluated hybrids.…”
Section: Chromosome Duplication Of Haploid Linesmentioning
confidence: 82%
“…This trait could be used to differentiate haploids and DHs from outcrossing plants (Borrino and Powell, 1988;Sood et al, 2003). A recent study in maize revealed that mean stomata length of haploid and DH plants at early stage (through leaf 1 to leaf 8 stage) is significantly smaller than that of the diploid controls (outcrossing seeds), thus indicating that stomata length together with anthocyanin color could be used to detect true haploids and DHs from control plants derived from outcrossing seeds (Choe et al, 2012).…”
Section: Plant Morphology and Stomatal Chloroplast Countmentioning
confidence: 98%